An in vitro study of a custom-made device for thermoregulation of the mixing slab on the setting properties of zinc oxide eugenol impression paste - Divyansh Sinha; Laasya Shivanand Shettigar; Kishore Ginjupalli; Nagaraja P Upadhya; Abhishek Bhagat (Wolters Kluwer Medknow Publications, 2023)
Aim: The present study was aimed to investigate the functional relationship between the mixing temperature and properties of a commercially available zinc oxide eugenol impression paste (ZnOE paste). Settings and Design: In-vitro study. Materials and Methods: A custom-made simulated mixing device was indigenously designed to maintain different mixing temperatures, simulating cold, ambient, and hot weather. A commercially available ZnOE paste was mixed according to the manufacturer's instructions in the simulated mixing device at the temperatures ranging from 10°C to 50°C. Initial setting time and consistency were measured according to A. D. A. Specification No. 16 (n = 8). A stainless-steel die having 25, 50, and 75 μm lines was used for surface detail reproduction. Detail reproduction of the stone casts of the impressions was evaluated with a stereomicroscope at 30 magnification (n = 8). The shear bond strength of ZnOE paste to self-cure acrylic tray resin was measured by using the UTM at a crosshead speed of 0.5 mm/min (n = 8). Statistical Analysis Used: Data were analyzed by using one-way analysis of variance (ANOVA) and Tukey's post hoc tests at a confidence interval of 95% (alpha =0.05) Results: Initial setting time, consistency, and detail reproduction of the ZnOE paste were affected by the mixing temperature (P < 0.001). Mixing ZnOE paste at a lower temperature of 10°C and higher temperatures of 40°C and 50°C resulted in shorter initial setting time, thicker consistency, and poor detail reproduction. However, no significant difference was obtained in the shear bond strength among the different mixing temperatures evaluated (P > 0.05). Conclusion: Based on this in vitro study, it is advisable to perform the manipulation of ZnOE paste at a clinical/laboratory temperature of 30°C for optimum performance. The simulated mixing device used in this study can be an alternative for extreme climatic conditions.